Structural heart disease in the newborn. Changing profile: comparison of 1975 with 1965. Issue 4 (April 1979) - Izukawa, T; Mulholland, H C; Rowe, R D; Cook, D H; Bloom, K R; Trusler, G A; Williams, W G; Chance, G W
Abstract : The earlier detection and investigation of babies with congenital structural heart disease has resulted in earlier treatment and better management of these patients. In 1965, at the Hospital for Sick Children, Toronto, 121 cases were assessed and treated; by 1975 this figure had risen to 226 cases. Few changes were noted in the incidence of the 10 most common malformations, except for the obvious increase in the incidence of patient ductus arteriosus due to survival of increasingly premature infants. The sick cardiac neonate was referred earlier in 1975, studied with newer non-invasive investigations, and, according to the severity of symptoms and signs, was sent sooner to cardiac catheterisation. 80% of babies presenting with cyanosis survived the first month and 60% of babies with congestive heart failure survived. With better surgery and perioperative care, the survival rate in the first month after surgery rose from 37% in 1965 to 70% in 1975.